Asymmetric pelvic and hip rotation in children with bilateral cerebral palsy: uni- or bilateral femoral derotation osteotomy? - Thielen, Mirjam; Döderlein, Leonhard; Klotz, Matthias C. M.; Braatz, Frank; Wolf, Sebastian Immanuel; Dreher, Thomas (Gait & posture, 2015)
Internal rotation gait is common among children with bilateral cerebral palsy. However, despite bilaterally increased femoral anteversion asymmetric internal rotation gait is often found. Femoral derotation osteotomy (FDO) is commonly performed bilaterally. Variable functional outcomes are reported especially in cases with mild internal hip rotation during gait and abnormal preoperative pelvic rotation. A major question is if a unilateral treatment of the more involved side in asymmetric cases leads to a comparable or even superior outcome. One hundred and nine children with spastic bilateral CP treated with FDO with pre- and 1-year postoperative 3D gait analysis were retrospectively collected. The asymmetry was calculated from the preoperative difference between both limbs in hip rotation obtained by 3D gait analysis. Twenty-eight children with asymmetry larger than 20° were selected and classified into two groups, according to whether they obtained a unilateral or bilateral FDO. Preoperative clinical examination and pre- and postoperative hip and pelvic rotation in gait analysis on the more and the less involved side did not differ significantly between both groups. Interestingly, in both groups, hip rotation did not change significantly in less-involved limbs, although intraoperative derotation averaged 25°. After unilateral FDO a significant change in pelvic rotation resulted, whereas this was not found after bilateral FDO. The results of this study suggest that unilateral FDO in children with asymmetric internal rotation gait leads to a comparable functional outcome compared to bilateral treatment. Furthermore, it was shown for the first time that considering the asymmetry has a positive effect on pelvic rotation.